Compulsive Disorder in Border Collie bitch - Rosado, Isabel Rodriges; da Silva, Juliana Gonzaga; de Freitas, Dilmas Mendes; dos Reis, Aline Silva; Picelli, Julia Perinotto; Leonel Alves, Endrigo Gabellini; Martins, Ian (Acta Scientiae Veterinariae, 2019)
Background: Compulsive disorders are excessive and repetitive behaviors that jeopardize the quality of life of both animal and tutor. It generally affects dogs between 6 and 36 months of age, and its etiology is associated to stress, anxiety and genetic predisposition. Clinical manifestations are the usual behaviors of the dog, but overly and inappropriately done. Diagnosis is based on a history of repetitive behavior, and on clinical and complementary exams to discard other diseases. The aim of this study is to report a case of compulsive disorder in a female Border Collie dog, including diagnostic and therapeutic approaches. Case: A 5-month-old, female, Border Collie dog was presented to Uberaba’s Veterinary Hospital (HVU) owing to a chasing shadows behavior that started as a playtime activity but intensified to the point of becoming a repetitive and excessive act, followed by self-trauma and excessive barking. Clinical examination showed lesions in nasal planum region. No alterations were observed on neurological examination apart from the chasing of shadows that also happened in the consultation room. Therefore, since there were no other findings on clinical and neurological exams, and since the manifestation occurred as a response to environmental stimuli (presence of shadows), it was established a presumptive diagnosis of compulsive disorder. Treatment with trazodone chlorhydrate was performed, and it was indicated ovariohysterectomy, a follow-up with a professional behaviorist and trainer and environment modifications. After a fortnight, it was observed a discreet improvement of the clinical signs, hence a second anxiolytic, clomipramine, was added to the treatment. Approximately 3 months after the beggining of therapy, there was improvement of the animal’s clinical picture, being calmer and most days ignoring the shadows. Discussion: Compulsive disorders are described as exaggerated and repetitive behaviors that jeopardize the animal’s interaction with its environment and with its tutor. The animal of this report showed repetitive behavior of chasing shadows, with claw abrasion and self-inflicted nasal lesions caused by leaping and biting on the surfaces where the shadows were projecting. Additionally, during the manifestation of the behavior, the animal barked excessively, which compromised the quality of the tutors’ lives. The patient was a Border Collie female dog, though there are no descriptions of this type of behavior in this breed. The starting age of this patient’s manifestations is consistent with previous reports, which observed it more frequently in animals with 6 to 36 months of age. The absence of alterations on clinical and neurological exams that could indicate maladies in other systems, in addition to a detailed anamnesis and assessment of videos of the animal recorded in his domicile, enabled the diagnosis of compulsive disorder. Ovariohysterectomy was done with the purpose of reducing the previously mentioned behavior. Drug therapy in addition to behavior training were efficient to promote significant improvement, although the duration of treatment is a long-term one, as described by other authors. Further studies are necessary for enlightenment of compulsive disorder’s physiopathology in dogs, and to investigate and identify the causes, such as environmental factors and genetic characteristics, that trigger these behaviors.